2017
DOI: 10.1177/1558944717744336
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Distal Interphalangeal Ganglion Cysts by Volar Corticosteroid Injection

Abstract: For patients with DIP ganglion cysts, this newly described technique of volar, transtendon, intra-articular injection of corticosteroid provides a safe and effective treatment. This technique allows for ease and consistency of needle placement for intra-articular corticosteroid delivery while minimizing the potential soft tissue and infection concerns described with other techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…CS can additionally lead to side effects such as skin thinning and depigmentation [44]. Weinheimer et al recently showed however that intra-articular corticosteroid injections may be useful in a certain type of ganglion cyst, a distal interphalangeal (DIP) cyst, which is associated with OA [45]. This study used a new technique by injecting 1 ml of dexamethasone 4 mg/ml and 1% lidocaine in equal proportions into the volar flexion crease above the DIP joint; this method allows for increased precision of needle placement into the joint, reduction of side effects associated with steroids, and a success rate equivalent with the literature currently [45].…”
Section: Injection Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…CS can additionally lead to side effects such as skin thinning and depigmentation [44]. Weinheimer et al recently showed however that intra-articular corticosteroid injections may be useful in a certain type of ganglion cyst, a distal interphalangeal (DIP) cyst, which is associated with OA [45]. This study used a new technique by injecting 1 ml of dexamethasone 4 mg/ml and 1% lidocaine in equal proportions into the volar flexion crease above the DIP joint; this method allows for increased precision of needle placement into the joint, reduction of side effects associated with steroids, and a success rate equivalent with the literature currently [45].…”
Section: Injection Techniquementioning
confidence: 99%
“…Weinheimer et al recently showed however that intra-articular corticosteroid injections may be useful in a certain type of ganglion cyst, a distal interphalangeal (DIP) cyst, which is associated with OA [45]. This study used a new technique by injecting 1 ml of dexamethasone 4 mg/ml and 1% lidocaine in equal proportions into the volar flexion crease above the DIP joint; this method allows for increased precision of needle placement into the joint, reduction of side effects associated with steroids, and a success rate equivalent with the literature currently [45]. Overall, the use of steroid injections with aspiration should not be recommended for most types of ganglion cysts until further research with different injection techniques is performed and verified.…”
Section: Injection Techniquementioning
confidence: 99%
“…DMC are often asymptomatic, but occasionally pain and tenderness are experienced, as well as nail deformities and decreased ROM. Although several conservative therapies have been performed, including expression of cystic contents, cryosurgery, CO 2 laser therapy, steroid/sclerosant injection, and infrared coagulation 12–17 , surgical excision management is the first‐line treatment because of its high cure rate 5 .…”
Section: Introductionmentioning
confidence: 99%